ARABISME DALAM PENAFSIRAN AL-QUR'AN - Sadig, Muhammad (Program Studi Ilmu Al-Qur'an dan Tafsir, Universitas Islam Negeri Datokarama Palu, 2021)
The writing of this article began with several arguments by Muslim scholars such as Nasr Hamid Abu Zaid who explained that the text was strongly influenced by the culture in which the text appeared or the opinion of A. Khalafullah who said that several Arab traditions were included in Islamic teachings. So the author wants to examine whether it is true that these cultures are able to influence the revelation of the Qur'an or not? Of course the research wants to explain that the Qur'an as the holy book of Muslims even though it is influenced by Arabic culture, but that culture is still relevant to Islamic teachings. Even some of the results of the author's research contained Islamic teachings that had no influence on Arab culture at that time. Therefore, the author wants to discuss this with the discussion of Arabism in the interpretation of the Qur'an using the library research method, the author will discuss this problem. As a result, the authors found several things that became Arab cultural traditions in the interpretation of the Qur'an, for example in terms of language, namely the Quraish language.